Modeling financial market dynamics with the use of fuzzy - K. A. Polekhina; G. Eu. Polekhina (Вестник университета)
In   the modern world, financial markets play an   important role in   the economy and people’s lives. They provide access to   financial resources and are also a   source of   profit for many companies. However, instability in  the financial markets can lead to   serious consequences such as   financial crises and loss of   investor confidence. In   this regard, modelling the financial market dynamics becomes increasingly relevant. This work considered the use of   fuzzy mathematics for this purpose. Fuzzy mathematics is a   branch of   mathematics that studies methods and algorithms for dealing with fuzzy data and fuzzy objects. It   allows to   consider uncertainty and incompleteness of  information, which is  especially important in  the financial markets where data is   often incomplete and inaccurate. The purpose of   this research is   to establish the relationship between financial asset prices while using behavioural factors (investor sentiment), fundamental (market returns), and microstructural ones (company size, ratio of   book and market values of   the company). The application of   fuzzy mathematics in   financial modelling will improve the accuracy and reliability of   forecasts as   well as   increase the stability of   the model to   various sources of  uncertainty.